Athletic Cardiac Adaptation in Males Is a Consequence of Elevated Myocyte Mass - McDiarmid, Adam K. (Circ Cardiovasc Imaging, 2016)
BACKGROUND—: Cardiac remodeling occurs in response to regular athletic training, and the degree of remodeling is associated with fitness. Understanding the myocardial structural changes in athlete’s heart is important to develop tools that differentiate athletic from cardiomyopathic change. We hypothesized that athletic left ventricular hypertrophy is a consequence of increased myocardial cellular rather than extracellular mass as measured by cardiovascular magnetic resonance. METHODS AND RESULTS—: Forty-five males (30 athletes and 15 sedentary age-matched healthy controls) underwent comprehensive cardiovascular magnetic resonance studies, including native and postcontrast T1 mapping for extracellular volume calculation. In addition, the 30 athletes performed a maximal exercise test to assess aerobic capacity and anaerobic threshold. Participants were grouped by athleticism: untrained, low performance, and high performance ([Image: see text] O(2max) <60 or>60 mL/kg per min, respectively). In athletes, indexed cellular mass was greater in high- than low-performance athletes 60.7±7.5 versus 48.6±6.3 g/m(2); P<0.001), whereas extracellular mass was constant (16.3±2.2 versus 15.3±2.2 g/m(2); P=0.20). Indexed left ventricular end-diastolic volume and mass correlated with [Image: see text] O(2max) (r=0.45, P=0.01; r=0.55, P=0.002) and differed significantly by group (P=0.01; P<0.001, respectively). Extracellular volume had an inverse correlation with [Image: see text] O(2max) (r=−0.53, P=0.003 and left ventricular mass index (r=-0.44, P=0.02). CONCLUSIONS—: Increasing left ventricular mass in athlete’s heart occurs because of an expansion of the cellular compartment while the extracellular volume becomes relatively smaller: a difference which becomes more marked as left ventricular mass increases. Athletic remodeling, both on a macroscopic and cellular level, is associated with the degree of an individual’s fitness. Cardiovascular magnetic resonance ECV quantification may have a future role in differentiating athlete’s heart from change secondary to cardiomyopathy.